2019
DOI: 10.1093/ofid/ofz401
|View full text |Cite
|
Sign up to set email alerts
|

Fall History and Associated Factors Among Adults Living With HIV-1 in the Cape Winelands, South Africa: An Exploratory Investigation

Abstract: Background People with HIV-1 (PWH) exhibit a high fall incidence and increased fracture risk. As little is known about fall frequency and associated factors in PWH residing in lower-middle-income countries (LMIC), we investigated fall frequency, bone quality, and factors associated with fall history in a South African cohort. Methods Fifty PWH without obvious predisposing factors for mobility impairments attending 2 public pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 36 publications
0
13
0
1
Order By: Relevance
“…Therefore, factors related to ageing may have influenced the prevalence of falls in the seronegative participants as well. One Ph.D. thesis 39 showed that falls were a problem in a relatively younger cohort of PLWH (median age of 36.61 years) living in a rural district of South Africa. A higher prevalence of falls in PLWH compared with the SNP was reported (34% PLWH vs 16% SNP; p=0.038).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, factors related to ageing may have influenced the prevalence of falls in the seronegative participants as well. One Ph.D. thesis 39 showed that falls were a problem in a relatively younger cohort of PLWH (median age of 36.61 years) living in a rural district of South Africa. A higher prevalence of falls in PLWH compared with the SNP was reported (34% PLWH vs 16% SNP; p=0.038).…”
Section: Discussionmentioning
confidence: 99%
“…[17] Three cross-sectional studies [30][31][32] in highincome countries reported falls prevalence ranging from 18.6% -40.7% in middle-aged to older PLWH. In LMIC, falls may be prevalent in younger cohorts of PLWH due to the different sociodemographic profile of PLWH or more virulent strains of Clade C HIV; [33] one recent South African study [34] attesting to this possibility. Hence, while Greene et al [4] recommended routine screening for falls in all PLWH who are 50 years and older, physiotherapists may need to assess for falls in both younger and older PLWH in LMIC.…”
Section: Improve Awareness Of Falls Among Plwh By Physiotherapistsmentioning
confidence: 99%
“…[41] The physiotherapists mostly relied on less precise X-rays; perhaps because they were more available and less expensive. One study [42] demonstrated calcaneal quantitative ultrasound (QUS) as a feasible alternative to DXA in screening BMD in PLWH, and Berner et al [34] used it successfully in a resource-limited setting. Perhaps primary health facilities can consider investing in this 'cost effective, portable and ionizing-radiation free tool' [2] to enable PLWH to be routinely screened for bone loss.…”
Section: Increase Use Of Standardised Screening Tools and Outcome Meamentioning
confidence: 99%
“…Increased longevity and increased HIV prevalence resulting from improved ART access implies that more PLWH are ageing with the condition, while fall rates similar to older adults in the general population have been reported in middle-aged PLWH (Ruiz et al, 2013). Studies from high-income countries (HICs) report a fall prevalence in middle-aged and older PLWH ranging from 12 to 41% (Richert et al, 2014;Erlandson et al, 2019); while preliminary findings from a recent South African study reported a prevalence of 34% among a relatively younger cohort of PLWH (median age = 36.61 years) (Berner et al, 2019). Reduction in bone mineral density (BMD) related to exposure to antiretroviral drugs as well as viral infection of osteoblasts have been observed in PLWH (Yin and Falutz, 2017).…”
Section: Introductionmentioning
confidence: 99%